CONSUMER PURCHASE DECISION ANALYSIS OF KEBAYA SYMPHONY PRODUCTS: THE ROLE OF GREEN MARKETING MIX - Adjeng. Mariana Febrianti; Fauzi Abdurasyid (JURNAL DARMA AGUNG, 2023)
This study aims to determine the effect of green marketing mix (green product, green price, green place, and green promotion) on purchasing decisions on Kebaya Symphony products in the city of Bali. This type of research uses a quantitative approach. The sample in this study was 95 consumer respondents in the city of Bali with purposive sampling technique. Data analysis used multiple linear regression. The results show that of the four green marketing mix variables, green products and green promotion are important elements in influencing consumer decisions in choosing natural color kebayas. While the other two variables (green price and green place) have no influence on consumer decisions. From these results, marketers or SMEs must develop more displays, samples and distributions so that elements of green marketing can be used as strategies in business sustainability.